An investigation into the reclamation of sewage effluent as a source of water supply to the Cape Metropolitan area - Kapp, J. F.(Johannes Francois) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1979.